2018
DOI: 10.1021/acs.jchemed.7b00964
|View full text |Cite
|
Sign up to set email alerts
|

Capstone Laboratory Experiment Investigating Key Features of Palladium-Catalyzed Suzuki–Miyaura Cross-Coupling Reactions

Abstract: This two-part laboratory experiment is concerned with investigating key aspects of the Suzuki–Miyaura cross-coupling reaction. The first part of this experiment utilizes high-throughput experimentation techniques to reinforce, explore, and extend fundamental concepts that are presented in the classroom. In contrast, the second part employs guided-inquiry learning strategies to challenge students to design, set up, and perform a preparative-scale Suzuki–Miyaura reaction and suggest workup and isolation protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In a recent study, , we identified that the poor turnover of key on-cycle intermediate trans -[Pd­(PPh 3 ) 2 (Ar)­(I)] in the presence of free PPh 3 was responsible for the surprisingly poor reactivity of aryl iodides in [Pd­(PPh 3 ) 4 ]-catalyzed Suzuki–Miyaura cross-couplings performed at relatively low temperatures (Scheme A,B) . Our report also illustrated the drastic difference between this process and the equivalent reaction utilizing aryl bromides (Scheme A).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, , we identified that the poor turnover of key on-cycle intermediate trans -[Pd­(PPh 3 ) 2 (Ar)­(I)] in the presence of free PPh 3 was responsible for the surprisingly poor reactivity of aryl iodides in [Pd­(PPh 3 ) 4 ]-catalyzed Suzuki–Miyaura cross-couplings performed at relatively low temperatures (Scheme A,B) . Our report also illustrated the drastic difference between this process and the equivalent reaction utilizing aryl bromides (Scheme A).…”
Section: Resultsmentioning
confidence: 99%
“…1b The oxidative addition of aryl halides to phosphine-ligated Pd(0) complexes has been studied extensively, 5 and it is generally accepted that the relative rates for the oxidative addition of aryl halides (Ar−X) to these Pd(0) species typically follow the trend Ar−I > Ar−Br > Ar−Cl. 5b,6 While we were in the process of developing a new undergraduate laboratory experiment focused on exploring key features of the Suzuki−Miyaura reactions utilizing a Pd/ PPh 3 catalyst system, 7 we were intrigued by results that counterintuitively suggested the very poor reactivity of aryl iodides at ∼50 °C. This was in stark contrast to efficient couplings of the equivalent aryl bromides at the same temperatures.…”
Section: ■ Introductionmentioning
confidence: 90%
“…More recently, a second report in utilizing key features of HTE in a capstone experiment for a third-year undergraduate chemistry laboratory program was developed, in which a group of 3−4 students first designed a set of Suzuki−Miyaura reactions using phenylboronic acid and available aryl halides that vary in electronics and sterics using palladium(II) acetate, tri(o-tolyl)phosphine, sodium carbonate, and propan-1-ol as the solvent. 6 Each group then performed ∼4−5 of the Suzuki−Miyaura cross-coupling reactions (performed in duplicates) each using a Radleys parallel reactor. 6 The reaction was individually quenched and worked-up for gas chromatography (GC) analysis to quantify the success of each reaction by comparing the consumption of the electrophile against the internal standard added at the beginning of the reaction.…”
mentioning
confidence: 99%
“…6 Each group then performed ∼4−5 of the Suzuki−Miyaura cross-coupling reactions (performed in duplicates) each using a Radleys parallel reactor. 6 The reaction was individually quenched and worked-up for gas chromatography (GC) analysis to quantify the success of each reaction by comparing the consumption of the electrophile against the internal standard added at the beginning of the reaction. 6 Although this experiment is a great example of a guided-inquiry teaching method that allows some exposure to the concept of HTE, a more streamed-line approach that is closer to the state-of-the-art HTE methods that are currently being utilized in academic and industrial research laboratories would improve and enrich the learning experience.…”
mentioning
confidence: 99%
See 1 more Smart Citation